2014
DOI: 10.4174/astr.2014.87.3.139
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the surgical outcomes of laparoscopic versus open surgery for colon perforation during colonoscopy

Abstract: PurposeColonoscopy is a safe and commonly used method for the screening of colon cancer, but sometimes major complications, such as, colonic perforation or hemorrhage occur during the procedure. The aim of this study was to compare the surgical outcomes of laparoscopic and open surgery for colon perforation after colonoscopy.MethodsA retrospective review of patient records was performed on 25 patients with iatrogenic colon perforation during colonoscopy during the 7-year period from January 2005 to June 2012. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Other studies by Rothold et al [ 125 ] and Schloricke et al [ 127 ] also observed fewer postoperative complications and significantly shorter hospital stays when utilizing the laparoscopic approach. Similar studies with similar results were published by Coimbra et al [ 124 ] and Kim et al [ 128 ], although in these studies, delayed surgeries (> 24 h) and ostomy formation rates were more frequently observed in the open groups, with higher primary repair rates in the laparoscopic groups.…”
Section: Resultssupporting
confidence: 89%
“…Other studies by Rothold et al [ 125 ] and Schloricke et al [ 127 ] also observed fewer postoperative complications and significantly shorter hospital stays when utilizing the laparoscopic approach. Similar studies with similar results were published by Coimbra et al [ 124 ] and Kim et al [ 128 ], although in these studies, delayed surgeries (> 24 h) and ostomy formation rates were more frequently observed in the open groups, with higher primary repair rates in the laparoscopic groups.…”
Section: Resultssupporting
confidence: 89%
“…Especially, when the colonic perforation occurs during a colonoscopy, the bowel content in the colon is minimal because of the bowel preparation, and colonic tissue is generally healthy. Therefore, laparoscopic primary repair or even conservative treatment can be considered [ 7 ]. As in the case of colonoscopy-induced colon perforation, in the case of ARM-induced colon perforation, if spillage of bowel content is minimal and the perforation occurs in the mesenteric space, the subsequent symptoms of the patient are usually tolerable, so primary repair or conservative treatment can be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy emerged in the last decade as a therapeutic possibility in early-detected perforations including those with endoscopic failure, because of its many advantages: less postoperative complications, shorter lengths of hospital stay, smaller incision size and lower labor withdrawal time. 19 However, this technique was only adopted in the latest 2 patients in this series. The areas of perforation were easily localized and there was not extensive inflammation neither fecal contamination.…”
Section: Discussionmentioning
confidence: 99%